Characteristics of Transparent Conducting W‐Doped SnO2 Thin Films Prepared by Using the Magnetron Sputtering Method. Issue 4 (19th December 2014) - Yu, Shihui; Li, Lingxia; Sun, Zheng; Zheng, Haoran; Dong, Helei; Xu, Dan; Zhang, Weifeng; Zhou, X.‐D.
<x xml:space="preserve">Abstract</x> Tungsten‐doped SnO2 (WTO) thin films with a given thickness of about 300 nm have been prepared by magnetron sputtering with a substrate temperature in the range 400°C–700°C. The effects of substrate temperature on the structural, optical, and electrical properties and of WTO thin films have been investigated. A texture transition from (1 1 0) to (2 1 1) crystallographic orientations has experimentally been found by X‐ray diffraction measurements as substrate temperature is raised. It was found that all thin films showed smooth surface with no cracks and high transparency (>85%) with the optical band gap ranging from 4.22 to 4.32 eV. The mobility varied from 12.89 to 22.48 cm2·(V·s)−1 without reducing the achieved high carrier concentration of about 1.6 × 1020 cm−3. Such an increase in mobility is shown to be clearly associated with the development of (2 0 0) but concurrent degradation of (1 1 0) in WTO thin films.